‘The Path of Least Resistance’ as Agency grounded in Morality: Meeting Teaching and Research Expectations in an Asian Higher Education Context - Daron Benjamin Loo; Ritha Maidom; Esther Varah (Universiti Teknologi Mara, 2023)
This study presents an examination of agency grounded in morality that is enacted by university lecturers to meet teaching and research expectations at an Asian university. This form of agency is conceived as being on the path of least resistance, where there is an interest to meet various expectations in a higher education context. Through narrative inquiry, this study examined the reflections of Ritha and Esther collected through collaborative auto-ethnography. The reflections were prompted by four narrative frames and resembled a conversation. Subsequently, the reflections were analysed through the lens of socio-cultural constructivism, where intersubjectivities were drawn together to arrive at a meaningful interpretation of agency. Findings from this study include university lecturers’ reconfiguration of priorities to attend to students’ needs, discovering fulfilment in doing research, and taking an ethical stance towards meeting institutional expectations. These findings point towards a cultural attribute of teacher agency in an Asian setting, which warrants further exploration.